Reliability Index Of Creative Thinking Among Electrical Engineering Lecturers - Mohd Hisham, Mohd Hizwan; Aripin, Muhamad Afzamiman; Saud, Muhammad Sukri; Ishar, Mohamad Izzuan; Mohamed Sultan, Al Amin (Science And Engineering Research Support Society, 2019)
This paper aims to determine the reliability index for creative thinking among electrical engineering lecturers in vocational colleges. Lecturers are the backbone of the education system in technical education and the executor of the policies and goals that have been set by the government through the Ministry of Education. Creative thinking is one of the higher order thinking skills that involves both cognitive skills and dispositions. Empirical research suggest that people begin developing creative thinking at a very young age. Lecturers are thus urged to provide explicit instruction in creative thinking to teach how to transfer knowledge critically to students. In order to transfer creative thinking, the teacher should be infused with the sub-skills that contribute to the development of creative thinking.